MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI MEMBANGUN MENTAL KEWIRAUSAHAAN ISTRI PETANI TAMBAK YANG TERGABUNG DALAM ORGANISASI PKK DESA PASI KECAMATAN GLAGAH LAMONGAN - Eka Srirahayu Ariestiningsih; Dwi Faqihatus Syarifah Has (ACADEMICS IN ACTION Journal of Community Empowerment, 2019)
This Sosial Comunity activity to solve existing problems, in supporting efforts to increase family income, impact on improving family welfare through empowerment approaches, namely empowerment of women who are community Prospective Entrepreneurs, by developing entrepreneur spirit in mothers who are members of women organization and activities in Pasi Village. Among the activities carried out is to provide motivation to grow entrepreneur spirit to fish farmer's wives in order to have the spirit of entrepreneurship, have the skills to make business designs and establish Micro, Small and Medium Enterprises and subsequently produce superior products by processing the expected local food ingredients can increase income for the family so that they can improve the welfare of their families. By having an entrepreneurial spirit will change their mindset and motivation so they have the willingness to create and innovate so they can produce more valuable products, namely Sausage and nugget Nugget which are processed from milkfish commonly sold to collectors with a low price because of the lowest quality. The method used to implement the solution in order to solve the problems.The outputs expected to be realized from this activity are: (1) The growth of entrepreneurial spirit in women organization in Pasi and Pelesan to provide additional income to the family; (2) Ability to create a business plan in order to realize entrepreneur; (3) Establishment of Micro Small and Medium Enterprises Groups; (4) Having the ability and skills to process local food ingredients; (5) Women’s Organization ini Pasi Village are able to develop product marketing strategies.